Comparative color and surface parameters of current esthetic restorative CAD/CAM materials - Ferhan Egilmez; Gulfem Ergun; Isil Cekic-Nagas; Pekka Kalevi Vallittu; Lippo Veli Juhana Lassila (KOREAN ACAD PROSTHODONTICS, 2022)
PURPOSE. The purpose of this study was to derive and compare the inherent color (hue angle, chroma), translucency (TPSCI), surface gloss (Delta E*(SCE-SCI)), and surface roughness (R-a) amongst selected shades and brands of three hybrid CAD/CAM blocks [GC Cerasmart (CS); Lava Ultimate (LU); Vita Enamic (VE)].
MATERIALS AND METHODS. The specimens (N = 225) were prepared into square-shaped (12 x 12 mm(2)) with different thicknesses and shades. The measurements of color, translucency, and surface gloss were performed by a reflection spectrophotometer. The surface roughness and surface topography were assessed by white light interferometry.
RESULTS. Results revealed that hue and chroma values were influenced by the material type, material shade, and material thickness (P < .001). The order of hue angle amongst the materials was LU > CS > VE, whereas the order of chroma was VE > CS > LU. TPSCI results demonstrated a significant difference in terms of material types and material thicknesses (P <= .001). TPSCI values of the tested materials were ordered as LU > CS > VE. Delta E*(SCE-SCI) and R-a results were significantly varied amongst the materials (P < .001) and amongst the shades (P < .05). The order of Delta E*(SCE-SCI) amongst the materials were as follows LU > VE >= CS, whereas the order of R-a was CS >= VE > LU. CONCLUSION. Nano-ceramic and polymer-infiltrated-feldspathic ceramic-network CAD/CAM materials exhibited different optical, inherent color and surface parameters.